Students’ Speaking Obstacles in the Fourth Semester of English Education Study Program - Novirjayanty Muhajir; Indry Widyasti Anwar; Taib Latif (FKIP Universitas Khairun, 2024)
This study aims to determine students' speaking obstacles and how they overcome them in the fourth semester of the English language study program. One lecturer and twenty students were taken as research subjects in the fourth semester. This study uses a descriptive qualitative method for collecting and analyzing data. This research is conducted by providing observations and interviews as an instrument. The results of the study show that several obstacles faced by students are divided into two factors, namely internal factors and external factors. In terms of internal factors, there are seven obstacles faced by students in learning to speak such as lack of vocabulary, poor grammar, speaking anxiety, fear of making mistakes, low participation, low self-confidence, and mother tongue use. External factors are divided into two categories: environment and lecturer's personality. Students enhance their speaking skills through various methods, including joining an English club or course, forming groups for practice or discussion, learning on social media, listening to English songs and podcasts, and watching movies.